MANAJEMEN SUMBER DAYA MANUSIA MELALUI PEMBIASAAN TADARUS AL-QUR’AN PADA SETIAP AWAL PEMBELAJARAN DALAM PERSPEKTIF PENDIDIKAN KARAKTER - Asmani Arif; Farid Wajdi (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Islamic learning in emphasizing the formation of character in each individual is the mission of the chosen human messenger ordered by God to improve human behavior. The purpose of this study was to find out the results of tadarus habituation (reading, studying, and understanding) of the Al-Qur’an for students which were carried out at the beginning of class learning. Is this habit also carried out at home? The method used in this study is a type of qualitative exploration. The source of the data is the results of student interviews regarding the habit of reciting the Koran applied in class, and whether it is also used at home. The results showed that many students did not practice reading the Koran as a habit in class when they were going to do learning. The value of character education in the habit of reading the Koran includes religious values, discipline, independence, communication, peace-loving, fondness of reading, and responsibility. These values function as the management of human resources in the framework of forming cultured human beings with a national character.